ANÁLISIS DEL LENGUAJE COMUNICACIONAL EN LA DIFUSIÓN DE LAS NOTICIAS EN EL “DIARIO LA HORA” CANTÓN QUEVEDO AÑO 2022. - Fuentes Riquero, Josselyn Johanna (2022)
The media have been systems that are used to transmit information, fulfilling the important task of reporting news. In Ecuador, the media range from the written press, television, radio, which over time have been evolving and adapting to new communication trends such as the incorporation of technology that allows them to produce, edit, generate live links in question. of minutes, facilitating journalistic tasks for all those who work in the different information media. The objective of the present investigation is to analyze the communicational language in the dissemination of the news in the "Diario La Hora" Quevedo canton year 2022, For the development of the investigation, and selection of the information was applied, the methods and types of investigation descriptive, explanatory, analytical that allow selecting data demonstrating the scope and results of the investigation where it indicates that, being a means of communication that is popular, it must make use of the most appropriate linguistic resources, for the use of a vocabulary, precise, simple, you will see reporting objectively by providing knowledge to the public, respecting the truth and acting with professionalism in the area that corresponds and as determined by law; In conclusion, Daario La Hora must analyze and correct errors, apply training policies, editorial manuals to develop and publish information with property, accuracy, authenticity, impartially, as journalistic work characterizes, to be recognized as a means of communication. reliable for society.